2021
DOI: 10.1108/ijbm-09-2020-0499
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mental budgeting and pain of payment on the financial decision making of socially excluded people

Abstract: PurposeConsumers who experience social exclusion often prefer high-risk financial products over low-risk financial products. The aim of this study is to examine how this effect can be attenuated by applying the theories of mental budgeting and pain of payment. The authors’ aim in pursuing this research is to improve the effectiveness of financial professionals and others in educating consumers on healthy financial practices. Understanding how social exclusion experiences influence financial decision-making is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…Several situational variables were identified that can attenuate or exacerbate pain of payment. Consumers experience lower levels of pain of payment when earning money is easy (vs. difficult) for them, for example, when they have an easy (vs. difficult) job (Bagchi & Block, 2011; Soster et al, 2014), when they feel in control of a consumption situation (Wagner et al, 2022), when they feel socially included (Chun & Johnson, 2021), when an expense is anticipated (vs. unanticipated; Besharat & Nardini, 2018), and as more time elapses from when consumers set a budget and when they make a purchase that falls into that budget category (Choe & Kan, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several situational variables were identified that can attenuate or exacerbate pain of payment. Consumers experience lower levels of pain of payment when earning money is easy (vs. difficult) for them, for example, when they have an easy (vs. difficult) job (Bagchi & Block, 2011; Soster et al, 2014), when they feel in control of a consumption situation (Wagner et al, 2022), when they feel socially included (Chun & Johnson, 2021), when an expense is anticipated (vs. unanticipated; Besharat & Nardini, 2018), and as more time elapses from when consumers set a budget and when they make a purchase that falls into that budget category (Choe & Kan, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to consumer behavior outcomes outlined above, anticipated pain of payment can influence consumer beliefs and perceptions. Higher anticipated pain increases consumers' preferences for low (vs. high) risk investments (Chun & Johnson, 2021). When purchasing food products, paying with more painful payment methods (i.e., cash vs. credit and debit cards) increases anticipated pain evoked by contemplating vice (vs. virtue) food purchases and increases the perception of health risks associated with consuming vice (vs. virtue) food products.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2019; Mainardes et al. , 2017) and by online panel companies (Bayuk and Altobello, 2019; Chun and Johnson, 2021; Song et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%